SYNTHESIS AND CHARACTERIZATION OF CaO PREPARED FROM LIMESTONE USING SOL-GEL METHOD - Munawaroh, Fatimatul; Masdya, Yoga; Baqiya, Malik Anjelh; Triwikantoro, Triwikantoro (Universitas Mataram, 2024)
The sol-gel method has been successfully applied to the synthesis and characterization of calcium oxide (CaO) derived from calcite-based natural limestone from Pamekasan, Madura, East Java Indonesia. Controlled dissolution, titration, gel formation, and subsequent calcination at temperatures 650°C and 900°C were the steps involved in the synthesis. X-ray diffraction was used for characterization to identify the phase that had formed. Supporting software, MATCH! used to analyze the phases and structures and Rietica for refinement using the Rietveld method. The Ca(OH)2 phase formed was 59.65 ± 2.45 %wt before the calcination process, according to the XRD results. 23.71 ± 0.61 %wt CaO was produced by the calcination process at 650°C, and 64.52 ± 1.85 %wt was produced at 900°C. Meanwhile, after calcination at 900°C, crystal size analysis using MAUD software produced CaO with a size of 534 ± 74 nm. K CaO powder synthesized using the sol-gel method is calcined at 900°C to get a higher percentage than at 600°C. The CaO powder can be used for CO2 capture applications because it comes from natural resources and is environmentally friendly.